2020
DOI: 10.1186/s40163-020-00121-w
|View full text |Cite
|
Sign up to set email alerts
|

Crime and coronavirus: social distancing, lockdown, and the mobility elasticity of crime

Abstract: Governments around the world restricted movement of people, using social distancing and lockdowns, to help stem the global coronavirus (COVID-19) pandemic. We examine crime effects for one UK police force area in comparison to 5-year averages. There is variation in the onset of change by crime type, some declining from the WHO 'global pandemic' announcement of 11 March, others later. By 1 week after the 23 March lockdown, all recorded crime had declined 41%, with variation: shoplifting (− 62%), theft (− 52%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
184
2
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(209 citation statements)
references
References 16 publications
13
184
2
10
Order By: Relevance
“…shoplifting) and a sharp increase and subsequent decrease in commercial burglary. Halford et al ( 2020 ) used Google Covid-19 Community Mobility Reports to estimate the elasticity of crime to measure responsiveness to social restrictions imposed in a United Kingdom police service. They found that elasticities varied by crime type.…”
Section: Related Researchmentioning
confidence: 99%
“…shoplifting) and a sharp increase and subsequent decrease in commercial burglary. Halford et al ( 2020 ) used Google Covid-19 Community Mobility Reports to estimate the elasticity of crime to measure responsiveness to social restrictions imposed in a United Kingdom police service. They found that elasticities varied by crime type.…”
Section: Related Researchmentioning
confidence: 99%
“…For example, increased time spent at the home might be expected to raise the opportunities for child abuse and domestic violence as the potential victims are spending more time together. 39 The list of nation-wide lock-down deaths in India during Covid-19 pandemic is presented in Table 1. Sleep disturbances, distress, anxiety, depression, and suicides were also reported in other Asian countries, Africa, Australia, Europe, North and South America due to Covid-19. 40 The psychiatric effect of Covid-19 poses increased the risk of suicide and other distress for months and years ahead.…”
Section: Suicidal Casesmentioning
confidence: 99%
“…However, most studies did not explicitly examine the association between changes in mobility and changes in crime, and instead used discrete before and after periods to identify changes in crime patterns. Two exceptions are Mohler et al (2020) and Halford et al (2020), who in addition to using discrete time periods, also examined the relationship between crime There are, however, important limitations to these studies. The first is that the Google mobility indices are only available from early 2020, thus it is not possible to examine the relationship between crime and mobility over a longer time period.…”
Section: Routine Activities Lockdowns and Crimementioning
confidence: 99%
“…The potential effects of pandemic-related lockdowns on crime have generated much academic interest. However, to date little research has been conducted outside of a few select countries that tend to be over-represented in criminological research: the US (Ashby, 2020a(Ashby, , 2020bCampedelli, Aziani, & Favarin, 2020;Mohler et al, 2020;Piquero et al, 2020;Shayegh & Malpede, 2020), Europe (Buil-Gil, Miró-llinares, Moneva, & Díaz-Castaño, 2020;Gerell, Kardell, & Kindgren, 2020;Halford, Dixon, Farrell, Malleson, & Tilley, 2020), and Australia (Payne, Morgan, & Piquero, 2020).…”
Section: Introductionmentioning
confidence: 99%